IMPLEMENTASI METODE TRANSPORTASI DALAM OPTIMASI BIAYA DISTRIBUSI PRODUK KARET PADA PT. IRC INOAC INDONESIA - Sri Lestari; Gala Ilmi Mustari; Zaenal Muttaqien (Universitas Muhammadiyah Tangerang, 2023)
PT. IRC Inoac Indonesia is a manufacturing company with the main products made from rubber base materials. Fulfilling the demand of costumers, of course, the company needs to distribute products as efficiently as possible. Distribution costs are the main focus of the company, because the company only performs cost calculations manually and the determination of routes and transportation networks that are still done manually. In the final task research, it aims to find optimal costs and efficient transportation routes and networks so that the company gets maximum profit. The methods used in this study with the initial solutions are North West Corner, Least Cost and Vogel’s Approxmations Method and supported by the final solution namely Stepping Stone and Modified Distributions. The company's initial distribution fee is Rp.15,894,450,-, after the trial is obtained the initial solution distribution cost of North West Corner amounting to Rp. 12,252,980,-, Least Cost amounted to Rp. 12,255,300,-, Vogel’s Approxmations Method amounted to Rp. 12,243,600,-. While the optimality test of Stepping Stone and Modified Distributions from the three initial solutions obtained the same result of Rp. 12,243,600,-. Based on the final results of this study, the company was able to save costs in June 2021 amounting to 23% of the initial cost of distribution or Rp. 3,650,850,-.Keywords: North West Corner, Least Cost, Vogel’s Approxmations Method, Stepping Stone, Modified Distributions